Consistency Analysis Planning And Realization Using Government Budget In Semarang - Anisa, Luthfiyana Nur; Fafurida, Fafurida (Efficient: Indonesian Journal of Development Economics, 2020)
This study aims to analyze the consistency of planning and realization of the use of the Semarang City government budget in 2014-2018 AND to analyze the level of performance achievement in the 2014-2018 Semarang City government budget. Data collection methods used in this research are documentation and literature study. The documentation method is a way of collecting data obtained from existing documents or records. The data used in this study is planning and realization of budgeting data, and performance in the form of secondary data and sourced from BPS and LHPBPK RILKPD Central Java. The results of this study are the highest consistency in the RKA and DPA documents. All programs and activities in the RKA and DPA are synchronized with each other. While the consistency between PPAS and RENJA and RENJA and RKA is still not consistent where there are additions or reductions in programs and activities in each of these documents, it means that the preparation of PPAS is not based on RENJA and the preparation of RKA is not based on RENJA completely. Analysis of performance achievements in the city of Semarang shows that in general the achievement of targets, programs and activities in the fiscal year cannot be realized 100%. Penelitian ini bartujuan untuk menganalisis konsistensi perencanaan dan realisasi penggunaan anggaran pemerintahan Kota Semarang tahun 2014-2018 DAN Untuk menganalisis tingkat capaian kinerja pada anggaran pemerintahan Kota Semarang tahun 2014-2018. Metode pengumpulan data yang digunakan dalam penelitian ini adalah dokumentasi dan studi pustaka. Metode dokumentasi merupakan suatu cara pengumpulan data yang diperoleh dari dokumen-dokumen yang ada atau catatan-catatan yang tersimpan. Adapun data yang digunakan dalam penelitian ini adalah data perencanaan dan realisasi penganggaran, serta kinerja yang berupa data sekunder dan bersumber dari BPS dan LHPBPK RILKPD Jateng. Hasil dari penelitian ini adalah Konsistensi tertinggi ada pada dokumen RKA dan DPA. Seluruh program dan kegiatan pada RKA dan DPA sinkron satusama lain. Sedangkan konsistensi antara PPAS dan RENJA maupun RENJA dan RKA masih kurang konsisten dimana adanya penambahan atau pengurangan program dan kegiatan pada setiap dokumen tersebut, berarti penyusunan PPAS tidak berlandaskan RENJA dan penyusunan RKA tidak berlandaskan RENJA sepenuhnya. Analisis capaian kinerja pada Kota Semarang menunjukkan bahwa secara umum pencapaian sasaran, program dan kegiatan pada tahun anggaran tidak dapat terealisasi 100%.